Assessment of chronic low‐dose elemental and radiological exposures of biota at the Kanab North uranium mine site in the Grand Canyon watershed. (27th September 2018) - Cleveland, Danielle; Hinck, Jo Ellen; Lankton, Julia S
ABSTRACT: High‐grade U ore deposits are in various stages of exploitation across the Grand Canyon watershed, yet the effects of U mining on ecological and cultural resources are largely unknown. We characterized the concentrations of Al, As, Bi, Cd, Co, Cu, Fe, Pb, Hg, Mo, Ni, Se, Ag, Tl, Th, U, and Zn, gross alpha and beta activities, and U and Th radioisotopes in soil, vegetation ( Hesperostipa comata, Artemisia tridentata, Tamarix chinensis ), and rodents ( Peromyscus maniculatus, P. boylii ) to waste material at the Kanab North mine, a mine with decades‐long surficial contamination, and compared the concentrations ( P < 0.01) to those at a premining site (Canyon Mine). Rodent tissues were also analyzed for radium‐226 and microscopic lesions. Radioactivities and some elemental concentrations (e.g., Co, Pb, U) were greater in the Kanab North mine biological samples than in Canyon Mine biota, indicating a mining‐related elemental signature. Mean rodent Ra‐226 (111 Bq/kg dry weight [dry wt]) was 3 times greater than expected, indicating radioactive disequilibrium. Multiple soil sample U concentrations exceeded a screening benchmark, growth inhibition thresholds for sensitive plants, and an EC20 for a soil arthropod. Lesions associated with metals exposure were also observed more frequently in rodents at Kanab North than those at Canyon Mine but could not be definitively attributed to U mining. Our results indicate that Kanab North biota have taken up U mining‐related elements owing to chronic exposure to surficial contamination. However, no literature‐based effects thresholds for small rodents were exceeded, and only a few soil and vegetation thresholds for sensitive species were exceeded; therefore, adverse effects to biota from U mining‐related elements at Kanab North are unlikely despite chronic exposure. Integr Environ Assess Manag 2019;15:112–125. Published 2018. This article is a US Government work and is in the public domain in the USA. Key Points: Small rodents and vegetation at Kanab North have taken up U mining‐related elements because of chronic exposure to surficial contamination, but no literature‐based effect thresholds for small rodents were exceeded, and only a few soil and vegetation thresholds for sensitive species were exceeded. Adverse effects to biota from U mining‐related elements at Kanab North are unlikely despite chronic exposure; however, aquatic pathways may provide an important route for trophic transfer and bioaccumulation of mining‐related elements at breccia pipe sites. Element sequestration in the roots and translocation of elements from the soil to the above‐ground vegetation might be considered during ground cover selection to minimize risk to browsers and grazers using reclaimed sites. These results may assist land managers in making resource decisions about relative U mining risks, approaches to site remediation, and resource protection.